Abstracts (Edited By Dr. Qasim Lateef Chaudhry) - Chaudhry, Qasim Lateef (Pakistan Journal of Ophthalmology, 2011)
Antagonism of Vascular Endothelial Growth Factor for Macular Edema Caused by Retinal Vein Occlusions: Two-Year Outcomes Hafiz G, Channa R, Shah SM, Nguyen QD, Ying H, Do DV, Zimmer – Galler I, Solomon SD, Sung JU, Syed B. Ophthalmology 2010; 117: 2387-94 Randomized Evaluation of the Trabecular Micro-Bypass Stent with Phacoemulsification in Patients with Glaucoma and Cataract Samuelson TW, Katz LJ, Wells JM, Pharm D, Duh YJ, Giamporcaro JE. Ophthalmology 2011; 118: 459-67. Central serous chorioretinopathy: an update on phathogenesis and treatment Gemenetzi M, Salvo GD, Lotery AJ. Eye 2010; 24: 1743–56.